CTDI-Based Assessment of Radiation Dose Output Accuracy in a 128-Slice CT Scanner Using Head and Body PMMA Phantoms - Mochamad Haris P; A. Santika Hyperastuty (Universitas Panca Marga, 2026)
Verification of Computed Tomography Dose Index (CTDI)-based dose output is essential for ensuring the accuracy of radiation delivery and supporting quality assurance in Computed Tomography (CT). This study aimed to verify the radiation dose output of a 128-slice CT scanner at the Radiology Department of RS Jiwa Menur Surabaya using CTDI measurements with standard PMMA head (16 cm) and body (32 cm) phantoms. Dose measurements were performed using a 100 mm pencil ionization chamber under standardized exposure parameters of 120 kV and 200 mA. CTDI100 values were measured at the center and peripheral positions of each phantom and subsequently used to calculate CTDIw and CTDIvol. The measured CTDI values were compared with the corresponding dose indices displayed by the CT scanner to determine the percentage deviation. The measured CTDIvol showed a deviation of 10.65% from the displayed value, while the body phantom exhibited a deviation of 10.16%. Although the measured CTDI values were consistently higher in the head phantom than in the body phantom due to differences in attenuation characteristics and phantom geometry, all deviations remained within the ±20% tolerance limit specified by BAPETEN regulations. These findings indicate that the CT scanner's dose output performance is consistent with the applicable regulatory acceptance criteria. Periodic CTDI-based verification is recommended to support ongoing quality assurance, maintain dosimetric accuracy, and optimize radiation protection practices in accordance with the ALARA principle.